C-peptide attenuates acute lung inflammation in a murine model of hemorrhagic shock and resuscitation by reducing gut injury. Issue 2 (August 2017) - Kao, Raymond L.C.; Xu, Xuemei; Xenocostas, Anargyros; Parry, Neil; Mele, Tina; Martin, Claudio M.; Rui, Tao
Abstract : BACKGROUND: The study aims to evaluate whether C-peptide can reduce gut injury during hemorrhagic shock (HS) and resuscitation (R) therefore attenuate shock-induced inflammation and subsequent acute lung injury. METHODS: Twelve-week-old male mice (C57/BL6) were hemorrhaged (mean arterial blood pressure maintained at 35 mm Hg for 60 minutes) and then resuscitated with Ringer's lactate, followed by red blood cell transfusion with (HS/R) or without C-peptide (HS/R + C-peptide). Mouse gut permeability, bacterial translocation into the circulatory system and intestinal pathology, circulating HMGB1, and acute lung injury were assessed at different times after R. The mice in the control group underwent sham procedures without HS. RESULTS: Compared to the sham group, the mice in the HS/R group showed increased gut permeability (6.07 ± 3.41 μg of FD4/mL) and bacterial translocation into the circulatory system (10.05 ± 4.92, lipopolysaccharide [LPS] of pg/mL), and increased gut damage; conversely, mice in the HS/R + C-peptide group showed significantly reduced gut permeability (1.59 ± 1.39 μg of FD4/mL; p < 0.05 ) and bacterial translocation (4.53 ± 1.08 pg of LPS/mL; p < 0.05) with reduced intestine damage. In addition, mice in the HS/R group had increased circulating HMGB1 (21.64 ± 14.17 ng/mL), lung myeloperoxidase) activity (34.4 ± 8.91 mU/g of tissue), and pulmonary protein leakage (2.33 ± 1.16 μg Evans blue/g tissue per minute). Mice in the HS/R + C-peptide group showed decreased HMGB1 (7.27 ± 1.93 ng/mL; p < 0.05 ), lung myeloperoxidase (23.73 ± 8.39 mU/g of tissue; p < 0.05), and pulmonary protein leakage (1.17 ± 0.42 Evans Blue/g tissue per minute; p < 0.05). CONCLUSION: Our results indicate that C-peptide exerts beneficial effects to attenuate gut injury and dysfunction, therefore diminishing lung inflammation and subsequent injury in mice with HS and R.